Effect of salt reduction on wheat-dough properties and quality characteristics of puff pastry with full and reduced fat content. (November 2016) - Silow, Christoph; Zannini, Emanuele; Axel, Claudia; Lynch, Kieran M.; Arendt, Elke K.
Abstract: Puff pastry is a major contributor of fat and sodium intake in many countries. The objective of this research was to determine the impact of salt (0–8.4 g/100 g flour) on the structure and quality characteristics of puff pastry with full and reduced (− 40%) fat content as well as the rheological properties of the resulting dough. Therefore, empirical rheological tests were carried out including dough extensibility, dough stickiness and GlutoPeak test. The quality of the puff pastry was characterized with the VolScan, Texture Analyzer and C-Cell. NaCl reduction significantly changed rheological properties of the basic dough as well as a number of major quality characteristics of the puff pastry. Significant differences due to NaCl addition were found in particular for dough resistance, dough stickiness, Peak Maximum Time and Maximum Torque (p < 0.05). Peak firmness and total firmness decreased significantly (p < 0.05) with increasing salt levels for puff pastry containing full fat. Likewise, maximal lift, specific volume, number of cells and slice brightness increased with increasing NaCl at both fat levels. Although a sensorial comparison of puff pastries revealed that salt reduction (30%) was perceptible, no significant differences were found for all other investigated attributes. Nevertheless, a reduction of 30% salt and 40% fat in puff pastry is achievable as neither the perception and visual impression nor attributes such as volume, firmness and flavour of the final products were significantly affected. Graphical abstract: Highlights: Salt reduction significantly influenced quality characteristics of the puff pastry. Salt reduction caused significant changes of rheological properties of basic dough. Firmness of full-fat pastries decreased significantly with increasing salt levels. Lift, specific volume and number of cells increased with increasing NaCl levels. No significant changes of major sensory attributes in fat and salt reduced pastries.